In Vitro Expanded Bioaccessibility of Quercetin-3-Rutinoside and Quercetin Aglycone from Buckwheat Biscuits Formulated from Flours Fermented by Lactic Acid Bacteria - Henryk Zieliński; Wiesław Wiczkowski; Joanna Honke; Mariusz Konrad Piskuła (MDPI AG, 2021)
The expanded bioaccessibility of rutin (Ru) and quercetin (Q) from buckwheat biscuits (BBs) formulated from liquid-state fermented flours by selected lactic acid bacteria (LAB) were determined after gastrointestinal digestion. Fermentation of buckwheat flours caused a LAB-dependent variation in Ru and Q content. BBs baked at 220 °C for 30 min showed lower content of Ru and Q, and no correlation was found between the content of these compounds in fermented flours and BBs. The expanded bioaccessibility of Ru from BBs was low when its content in the soluble and insoluble fractions remaining after digestion in vitro was taken into account. Contrary results were found for Q bioaccessibility which had an index greater than 1, indicating the high Q bioaccessibility from BBs. Since very low Q content was noted in the insoluble fraction remaining after BBs digestion, the high Q bioaccessibility was determined to be due to its concentration in the soluble fraction.